2014
DOI: 10.1134/s0018151x14030183
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of single droplets and dispersed liquid flow in motion through high-temperature combustion products

Abstract: Experimental study of the evaporation of single droplets and droplets in a flow of dispersed liquid in their motion through high temperature combustion products of a typical fuel is performed. The evapora tion rates of droplets of different sizes are compared; the characteristics of vaporization in a flow of dispersed liquid are analyzed. The conditions under which the drops moving first in the flow significantly slow the evap oration of the following drops are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 14 publications
1
51
0
1
Order By: Relevance
“…Other experimental investigation with using the setup (Fig. 2) for optical diagnostics of multiphase flows based on the PIV method [1,2] was carried out for the analysis of the ignition delay time values in a real technological process conditions and a more detailed study of heat and mass transfer in the vicinity of the coal particles.…”
Section: Experimental Studies and Resultsmentioning
confidence: 99%
“…Other experimental investigation with using the setup (Fig. 2) for optical diagnostics of multiphase flows based on the PIV method [1,2] was carried out for the analysis of the ignition delay time values in a real technological process conditions and a more detailed study of heat and mass transfer in the vicinity of the coal particles.…”
Section: Experimental Studies and Resultsmentioning
confidence: 99%
“…Exists numerous publications which are devoted, for example, to the investigation of droplet formation, their deformation, breakage, collisions, and evaporation [1][2][3][4]. Continuous change of shape and area occurs at the droplet surface drops deformation in flight.…”
Section: Introductionmentioning
confidence: 99%
“…The most common is the technology [7-12] of fragmentation of water droplets (or of any other quenching liquids) prior to the delivery to the fl ame zone to intensify steam generation. Experiments [13][14][15][16][17][18] showed that apart from the changing of the characteristic dimensions of droplets and of their dispersity, it is worthwhile to carry out a number of other operations, for example, preliminary heating of water, introduction of foreign solid inclusions and admixtures into water, and alternation of the velocities and trajectories of injection of a sputtered liquid.It has been established in numerical simulation [4-6] that the surface area of droplets (and, as a consequence, the steam generation surfaces) plays a decisive role in the processes of heat and mass transfer. The experiments in [13][14][15][16][17][18] have shown that this parameter depends substantially not only on the intensity of phase transformations, but also on the process of droplet deformation.…”
mentioning
confidence: 99%
“…The most common is the technology [7-12] of fragmentation of water droplets (or of any other quenching liquids) prior to the delivery to the fl ame zone to intensify steam generation. Experiments [13][14][15][16][17][18] showed that apart from the changing of the characteristic dimensions of droplets and of their dispersity, it is worthwhile to carry out a number of other operations, for example, preliminary heating of water, introduction of foreign solid inclusions and admixtures into water, and alternation of the velocities and trajectories of injection of a sputtered liquid.…”
mentioning
confidence: 99%